Effects of delayed weather radar images on pilots' spatial awareness. (January 2022) - Hua, Lesheng; Ling, Chen; Thomas, Rick
Abstract: Data-linked Next Generation Weather Radar (NEXRAD) images can be delayed up to 20 min in the cockpit. Pilots' underappreciating or ignoring the time delay may be the major cause of two fatal accidents. No studies have connected spatial awareness with accidents. This study evaluated how delayed radar information affects the spatial awareness of pilots at three levels of analysis. Thirty-one student pilots and flight instructors completed three sequential estimation tasks (i.e., the current location of storms, the current relative distance to storms, and the future relative distance to storms). Fifty-four weather scenarios were developed for three factors (storm speeds, delays, displays) and presented to pilots. The results indicated that delays and the storm speed significantly affected the three levels of spatial awareness. Participants' estimation accuracy was the lowest under long delay and fast speed in the current location estimation, under medium delay and speed in the current distance estimation, and under short delay and slow speed in the future distance estimation. Spatial awareness could be high under the long delay and fast speed conditions if pilots had no time limits. Thus, pilots can process 20-min delayed radar information. However, there were no differences in estimation accuracy between the static and animation displays in any of the conditions. Well-designed features on displays, such as scale or distance measuring tools, can aid pilots' spatial estimation and support all levels of spatial awareness. Highlights: The performance of three tasks can reflect three levels of awareness. The significant interaction exhibited difficulties in estimating distance under non-severe conditions. If there was no time stress, spatial awareness could be high under long delay and fast movement. Pilots could process 20-min delayed storm information. Well-designed display features helped pilots estimate non-severe conditions.